MODIFIKASI ALAT PANJAT UNTUK PEMANENAN NIRA PADA POHON AREN - Setiawan, Billiang; Widodo, Lamto; Ahmad (Jurnal Mitra Teknik Industri, 2025)
In the world of agriculture, it is known that there are many problems in every process of managing plants where every activity carried out by farmers has difficulties. Difficulties experienced by farmers include difficulties in climbing, cutting, picking, and others. One of the plants whose problems and solutions will be discussed is the palm tree (Arenga pinnata). The problem is that farmers experience pain when climbing sugar palm trees. The pain experienced by the farmer was the thumb, index finger and sole of the foot. Farmers initially climb by holding the bamboo as a ladder, then stepping into the bamboo hole using their thumb and forefinger, and their feet gradually to climb the bamboo. When entering the picking process, it is known that the farmer is sitting on one of the tree trunks that can support the farmer's weight. In the palm tree modification process, the Nordic Body Map and REBA methods were used to process the data. The REBA score when climbing was 10 points, when harvesting it was 11 points, and the Nordic Body Map was found to have the most pain on the left and right palms, mean while to create an innovation SCAMPER and SWOT are used. To get the desired results, it was found that the stairs had to be covered on the footing with a foot width of 10 cm at the 95 percentile and a foot thickness at the 95 percentile of 10 cm, then the difference in tread height was 30 cm.